Fuzzy Reliability Analysis of Contact Fatigue Strength of Planetary Gear Transmission - 李威; 孟惠荣; 常山; 陈谌闻 (Jixie chuandong)
In this paper,used fuzzy mathematical theory and reliability design method,the fuzzy reliability mathematical model of involute planetary gear transmission and its calculation formula are set up,the reliability design method of contact fatigue strength,when fuzzy variables and random variables simultaneously exist in gear design,is studied and some calculating example are given.The results show that the fuzzy reliability design is feasible and practical.